The Dilemma of Judicial Pardon in the Use of Medical Cannabis: A Criminal Law Perspective in Indonesia - Ni Putu Noni Suharyanti; Wedha, Yogi Yasa; Sutrisni, Ni Komang (Universitas Bali Dwipa, 2025)
Rechterlijk pardon is not explicitly mentioned in the nomenclature of the National Criminal Code, however, substantively / implicitly the arrangement is in Article 71 of Law Number 1 of 2023 concerning the Criminal Code, so that it is sufficient to provide legal certainty for judges in its application. This arrangement, it is possible to apply in the case of medical marijuana. As a response to public discourse and the dynamics of law and the development of science as well as the solution of creating a balance between fair law enforcement and recognition of urgent medical needs. Without leaving the integrity of the applicable law, carried out with the precautionary principle, and having true accountability. In addition, applying rechterlijk pardon in medical marijuana cases is an important step supported by the principles of humanity and human rights. By giving judges discretion to consider the individual circumstances of the accused, the judiciary can contribute to substantive justice. The criminal law implications of medical cannabis use in Indonesia create complex challenges but also offer opportunities for reforms that can improve access and protection for patients. By addressing legal uncertainty and inherent stigma, Indonesia can develop more humane policies and be responsive to public health needs. Constructive dialog between policymakers, legal experts, and the public is essential to balance law enforcement and the need for effective medical care.